STRATEGI SUPPLY-CHAIN MURABAHAH UNTUK PENGEMBANGAN INDUSTRI GENTENG DI JARINGAN USAHA KPPS NURI SAMPANG KOTA - Siti Masriyah (JSE: Jurnal Sharia Economica, 2025)
This research is motivated by the supply chain inefficiencies in the small-scale roof tile industry in Sampang, stemming from the atomistic murabahah financing pattern employed by KSPPS Nuri Jatim Sampang City Branch. This approach focuses solely on individual artisans without addressing the upstream and downstream links, leading to raw material supply uncertainty, price volatility, and weak competitiveness. Using a qualitative case study method involving interviews, observation, and document analysis, this study aims to formulate an integrated financing strategy. The findings map the fragile supply chain and propose a Supply-Chain Murabahah model that transforms the role of KSPPS Nuri from a mere funding provider to an active integrator. The model involves establishing a Cluster Development Team to coordinate linked murabahah schemes: financing for raw material suppliers to ensure stock and financing for artisans specifically tied to purchasing from this guaranteed supply. Implementation is recommended through a limited pilot project leveraging the existing high social capital. In conclusion, this model has the potential to create systemic stability, collective efficiency, and enhance the competitiveness of the fostered roof tile industry, while also contributing to the development of the Islamic Supply Chain Finance concept at the microfinance level.